Analysis of the effect on inflation, interest rate, dow jones Islamic Malaysia Index and profitability on stock prices as selected as Indonesia Sharia Stock Index - Sofyan Halim (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - The purpose of this study was to analyze what influences the change in the ISSI price index. The analysis was based on the phenomena and hypotheses that occur in the capital market by examining whether there is an influence of inflation rates, interest rates, and the Dow Jones Islamic Malaysia Index as external factors, as well as profitability such as Return on Assets and Earning per Share as internal factors that have an influence on changes and fluctuations in the Sharia Stock Index.Method - The population in this study are all stocks that are encoded in the Indonesia Sharia Stock Index (ISSI) listed on the Indonesia Stock Exchange. Based on the Sharia Stock Exchange and the number of shares indexed by ISSI was 408 shares which shares were classified into 11 types of business. The study was conducted by analyzing multiple regression with t-test, significance test, F test, and classical assumption test.Result - Based on the research results of bank interest rates and the Dow Jones Islamic Malaysia Index which affect stock prices indexed as Indonesia Sharia Stock, the two variables are the external influence of the issuers of the shares. And the majority of these stock prices are strongly influenced by variable factors not examined.Implication - This research indicates that the factors that influence stock prices indexed as Islamic stocks in Indonesia, the analysis of the coefficient of determination is not significant at 0.6%, to find out other factors, other variables are needed for further research.Originality  - This research is a continuation of previous research but uses different variables from previous researches, where the dependent variable is stock prices indexed as Indonesian Islamic stocks and the independent variable is the inflation rate, interest rate, and the Malaysian Islamic Dow Jones Index as factors.